High Prevalence of Clostridioides difficile Ribotype 176 in the University Hospital in Kosice - Katarina Curova; Martin Novotny; Lubos Ambro; Anna Kamlarova; Viera Lovayova; Vladimir Hrabovsky; Leonard Siegfried; Pavol Jarcuska; Peter Jarcuska; Annamaria Toporova (Pathogens, 2023)
Dysbiosis of the gut microbiota, caused by antibiotics, plays a key role in the establishment of Clostridioides difficile CD). Toxin-producing strains are involved in the pathogenesis of Clostridioides difficile infection (CDI), one of the most common hospital-acquired infections. We cultured a total of 84 C. difficile isolates from stool samples of patients hospitalized at Louis Pasteur University Hospital in Kosice, Slovakia, that were suspected of CDI and further characterized by molecular methods. The presence of genes encoding toxin A, toxin B, and binary toxin was assessed by toxin-specific PCR. CD ribotypes were detected using capillary-based electrophoresis ribotyping. A total of 96.4% of CD isolates carried genes encoding toxins A and B, and 54.8% of them were positive for the binary toxin. PCR ribotyping showed the presence of three major ribotypes: RT 176 (n = 40, 47.6%); RT 001 (n = 23, 27.4%); and RT 014 (n = 7, 8.3%). Ribotype 176 predominated among clinical CD isolates in our hospital. The proportion of RT 176 and RT 001 in four hospital departments with the highest incidence of CDI cases was very specific, pointing to local CDI outbreaks. Based on our data, previous use of antibiotics represents a significant risk factor for the development of CDI in patients over 65 years of age.